Efficacy of radiomics model based on the concept of gross tumor volume and clinical target volume in predicting occult lymph node metastasis in non-small cell lung cancer - Zeng, Chao; Zhang, Wei; Liu, Meiyue; Liu, Jianping; Zheng, Qiangxin; Li, Jianing; Wang, Zhiwu; Sun, Guogui (Frontiers in Oncology, 2023)
Objective This study aimed to establish a predictive model for occult lymph node metastasis (LNM) in patients with clinical stage I-A non-small cell lung cancer (NSCLC) based on contrast-enhanced CT. Methods A total of 598 patients with stage I–IIA NSCLC from different hospitals were randomized into the training and validation group. The “Radiomics” tool kit of AccuContour software was employed to extract the radiomics features of GTV and CTV from chest-enhanced CT arterial phase pictures. Then, the least absolute shrinkage and selection operator (LASSO) regression analysis was applied to reduce the number of variables and develop GTV, CTV, and GTV+CTV models for predicting occult lymph node metastasis (LNM). Results Eight optimal radiomics features related to occult LNM were finally identified. The receiver operating characteristic (ROC) curves of the three models showed good predictive effects. The area under the curve (AUC) value of GTV, CTV, and GTV+CTV model in the training group was 0.845, 0.843, and 0.869, respectively. Similarly, the corresponding AUC values in the validation group were 0.821, 0.812, and 0.906. The combined GTV+CTV model exhibited a better predictive performance in the training and validation group by the Delong test (p<0.05). Moreover, the decision curve showed that the combined GTV+CTV predictive model was superior to the GTV or CTV model. Conclusion The radiomics prediction models based on GTV and CTV can predict occult LNM in patients with clinical stage I–IIA NSCLC preoperatively, and the combined GTV+CTV model is the optimal strategy for clinical application.